Porous Carbon Materials for Clean and Sustainable Energy - GUO, Kelvii Wei (Review of Energy Technologies and Policy Research, 2018)
Carbon materials mostly involved in new alternative clean and sustainable energy technologies have been playing more and more significant role in energy storage and conversion systems, especially for the carbon porous materials, because carbon porous materials with structures can provide large surface areas for reaction, interfacial transport, or dispersion of active sites at different length scales of pores and shorten diffusion paths or reduce diffusion effect. Therefore, the soft, hard templated and hierarchically ordered strategies employed to fabricate porous carbon materials are marked along with the relevant advantages and disadvantages aim to provide the vital information about the growing field for future energy to minimize the potential environmental risks. Carbon porous materials with attractive structures as ideal candidates for the versatility and feasibility of application to energy storage and conversion should not only be realized, but also much effort has to be devoted to systematic studies on the relationship between physicochemical properties of these materials and their performances in energy conversion and storage to more efficiently stimulate further developments in this fascinating area, alongside eco-technologies that will ensure minimal environmental impact.